Applying a web-based self-help intervention for bulimia nervosa in routine care: study protocol for a randomized controlled trial - Hartmann, Steffen; Prüßner, Luise; Rubel, Julian; Lalk, Christopher; Barnow, Sven; Timm, Christina (Internet interventions, 2022)
Background - Individuals with bulimia nervosa (BN) experience persistent episodes of binge eating and inappropriate compensatory behavior associated with impaired physical and mental health. Despite the existence of effective treatments, many individuals with BN remain untreated, leading to a high burden and an increased risk of chronicity. Web-based interventions may help facilitate access to evidence-based treatments for BN by reducing barriers to the health care system. - Methods - The present study will investigate the effectiveness of a web-based self-help intervention for BN in a two-armed randomized controlled trial. Individuals diagnosed with BN (N = 152) will be randomly assigned to either (1) an intervention group receiving a 12-week web-based intervention or (2) a waitlist control group with delayed access to the intervention. Further assessments will be scheduled 6 (mid-treatment) and 12 (post-treatment) weeks after baseline. Changes in the number of binge eating episodes and compensatory behaviors will be examined as primary outcomes. Secondary outcomes include global eating pathology, functional impairments, well-being, comorbid psychopathology, self-esteem, and emotion regulation abilities. - Discussion - Adding web-based interventions into routine care is a promising approach to overcome the existing treatment gap for patients with BN. Therefore, the current study will test the effectiveness of a web-based intervention for BN under standard clinical care settings. - Trial registration - ClinicalTrials.gov, Identifier: NCT04876196 (registered on May 6th, 2021).